Fun with paper - Amery, Heather (New York Random House, 1993)
Includes instructions for making a variety of items with paper, such as flowers, pop-up cards, hats, and masks.
Originally published in Great Britain in 1993 by Hamlyn Children's Book, part of Reed Children's Books.
Keywords: Paper work -- Juvenile literature; Handicraft; Paper work